Effect of Lactic Acid and Irradiation on the Shelf Stability Characteristics of Hurdle Processed Chicken Legs - Jayathilakan, K.; Sultana, Khudsia; Radhakrishna, K.; Bawa, A.S. (International Journal of Poultry Science, 2009)
Hurdle processed chicken legs were subjected for irradiation at 1 and 2 KGy dosage levels after treatment with lactic acid (1 and 2%) to study the effect of irradiation and lactic acid on the shelf stability of the product. The products initially and during storage at 5oC were evaluated for its oxidative rancidity profile in terms of Thiobarbituric Acid Reactive Substances (TBARS), Total carbonyls and non-heme iron values. Lipid oxidation increased with reference to irradiation dosage and there was a significant difference (p